Poor Organ Donation in Vietnam: Resulting from Beliefs, Religions, and Traditional Culture? How to Promote Organ Donation and to Deal with Organ Trading from a Legal Perspective? - Chi, Le Lan (International Journal of Criminology and Sociology, 2021)
In Vietnam, organs are always in great demand while the organ supply from brain dead donors is extremely small, prompting the search for organs supplied by living people. People in need of an organ transplant either have to wait for a legally supplied organ (coming from any voluntary and non-commercial donation) or resort to an illegal supplied one (through organ trading). Therefore, increasing the number of legally supplied organs and controlling illegal source of supply are problems to be solved by Vietnam. This paper discovers whether religions, beliefs, traditional culture, and current legislation impede the organ donation or not. In addition, this paper also aims to find out legal loopholes resulting in ineffective handling of organ trading, then proposing solutions to improve the law to promote the legal supply of organs and effectively combat crimes related to organs illegally supplied by organ trading.